A study on the legal framework of asylum seekers and refugees: a comparative analysis between Malaysia and India / Mohd Rizal Ibrahim - Ibrahim, Mohd Rizal (2017)
This paper is a study on the legal framework of both countries namely Malaysia and India- two countries that have not ratified Convention Relating To The Status of Refugees and its Protocols 1967. Despite these two countries do not have full legal protection towards asylum seekers and refugees, yet both countries are still considered as main destinations of this group of people. This study covers what are legal rights and problems that asylumseekers and refugees in these countries face in the absence of specific laws. This study also recommends some measures that can be taken from and experiences that can be learnt especially by Malaysia from the experience of India in tackling asylum seekers and refugees management.